Benefícios econômicos agregados às propriedades urbanas pelas paisagens naturais - Azevedo, Nara Guimarães (2014)
Amenities value provided by green areas, sea, river and natural landscapes are hardly perceived and incorporated on urban planning and development. In this work, distance and view to protected and non-protected green areas, sea and river were evaluated as to how they increase the housing prices in Natal. Hedonic pricing methods were used with linear models to estimate the marginal implicit value of environmental, residential and neighborhood features. Results on Chapter 1 demonstrate the view to the sea and protected natural areas were largely capitalized on housing prices, while non-protected natural areas didn t display such effect. Housing prices also increase when close to the sea or to parks entrance. However, housing prices fall when houses are near non-protected natural areas. When estates with sea view were excluded, the protected natural areas view and a longer distance to non-protected natural areas increased dwelling prices. Results on Chapter 2 point the sea view as an hedonic variable the contributes strongly to the property selling prices, even though not always as the greatest contributor; furthermore, the property proximity to Dunas Park or City of the Park entrance increases its price, as does closeness to Dunas Park, view to City of the Park or Dunas Park. On the other hand, selling prices diminish if properties are close to City of the Park or Morro do Careca. Results on this study confirm the hedonic pricing methods is an important intrument, capable of revealing to popullation the importance of enviromental amenities and can be used by public managers for creating public policies for conservation and restoration projects